Pengelolaan Sampah Organik pada Pondok Pesantren Melalui Budidaya Maggot - Mukhibab, Hasan; Jayanto, Prabowo Yudo; Anisykurlillah, Indah; Nurkhin, Ahmad; Baswara, Satsya Yoga (State Islamic University of Mataram, 2025)
The problem faced by Islamic Boarding Schools is that waste management is not yet optimal. Most of this waste is from leftover food and other consumption by all students. The impact of this condition is the accumulation of school boarding waste, which is not utilized properly. Community Service Model with Participatory Action Research (PAR) approach through participatory training consisting of socialization, training, and implementation of organic waste management in Islamic boarding schools. Training activities will be continued with assistance until organic waste management has been running. Training materials include the basics of waste management. This service activity was carried out with lectures and maggot cultivation training involving 30 participants from Islamic boarding school students and residents. Participants were also invited directly to how to cultivate maggots. The results of the activity showed that participants had a good understanding of waste management, maggot cultivation, maggot maintenance, and maggot sales. Waste management begins with the sorting of organic and non-organic waste. Maggot cultivation begins with the purchase of maggot seeds and the provision of maggot food. Maggot sales include prisoners in the management of maggots to become products ready to be sold to consumers.